PENURUNAN DERAJAT STRES PASIEN KANKER TULANG STADIUM LANJUT DENGAN RESTRUKTURISASI KOGNITIF MENGGUNAKAN MEDIA AL-QURAN - Permana, Rizka Hadian (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
Maladaptive thoughts about cancer will cause a high degree of stress, which will worsen the health condition of the cancer patient. The purpose of this study was to obtain empirical data on the effect of cognitive restructuring using the QS Al-Anbiyaa:35 in an effort to reduce the degree of stress in patients with advanced bone cancer. The study was conducted using mix method model, to see differences in the degree of stress in patients. Based on the results of the study, it can be concluded that cognitive restructuring can change judgments, thoughts and maladaptive beliefs which have an effect on reducing stress levels.